Radio's second century : past, present, and future perspectives - Hendricks, John Allen, ....- (New Brunswick (N.J.) : Rutgers university press, 2020)
"As one of the first scholarly monographs to examine the status of broadcasting on its one hundredth anniversary, Radio's Second Century investigates both vanguard and perennial topics relevant to radio's past, present, and future. As the radio industry enters its second century of existence, it continues to be a dominant mass medium with almost total listenership saturation despite rapid technological advancements that provide alternatives for consumers. Lasting influences such as on-air personalities, audience behavior, fan relationships, and localism are analyzed as well as contemporary issues including social and digital media. Other essays examine the regulatory concerns that continue to exist for public radio, commercial radio, and community radio, and discuss the hindrances and challenges posed by government regulation with an emphasis on both American and international perspectives. Radio's impact on cultural hegemony through creative programming content in the areas of religion, ethnic inclusivity, and gender parity is also explored. Taken together, this volume compromises a meaningful insight into the broadcast industry's continuing power to inform and entertain listeners around the world via its oldest mass medium--radio"--
Digital radio : audio listening from AM to FM to XM ... and beyond / John Allen Hendricks and Bruce Mims -- Audience research and web features of radio stations in a time of uncertainty / Lu Wu and Daniel Riffe -- The parasocial nature of the podcast / Laith Zuraikat -- Social media analytics, radio advertising, and strategic partnerships / Joseph R. Blaney -- The shrinking electronic town square : localism in American talk radio / David Crider -- The fandom of Howard Stern and its relationship to his success : The "king of all media" and a dynamic audience / Rachel Sussman-Wander Kaplan -- The "War of the worlds" broadcast : fake news or engaging storytelling? / John F. Barber -- Unpredictable programming : a freeform approach to building audiences / Emily W. Easton -- Air to the kingdom : religion and the soul of radio / Mark Ward, Sr. -- "A more inclusive public service" : can NPR serve all of America? / John Mark Dempsey -- The sound of yellow rain : resisting podcasting's sonic whiteness / Anjuli Joshi Brekke -- Canadian community/campus radio : struggling and coping on the cusp of change / Anne F. MacLennan -- Revenge of the nerds : how public radio dominated podcasting and transformed listening to audio / Brad Clark and Archie McLean -- Reproducing analog pathologies in the digital radio landscape : the case of Greece / Michael Nevradakis -- Almost 100 years of women in radio : where are we now? / Simon Order.
Includes bibliographical references and index.
Keywords: Radio broadcasting; Radio; geschiedenis